State feedback control for a class of stochastic high-order feedforward nonlinear systems with time-varying delays: a homogeneous domination approach. (December 2014) - Jiao, Ticao; Cui, Guozeng; Lu, Junwei; Ma, Qian
In this paper, the problem of global state feedback stabilization for a class of stochastic high-order feedforward nonlinear systems with different power orders and multiple time delays is investigated. A distinct property of the system to be investigated is that the control coefficients are not restricted to 1. By adding one power integrator technique and homogeneous domination approach, a state feedback controller design is recursively proposed, which ensures the global asymptotical stability in probability of the closed-loop system. Finally, a simulation example is given to illustrate the effectiveness of our results obtained in this paper.